Exploring Indonesian adolescent women's healthcare needs as they transition to motherhood: A qualitative study. Issue 6 (December 2019) - Erfina, Erfina; Widyawati, Widyawati; McKenna, Lisa; Reisenhofer, Sonia; Ismail, Djauhar
Abstract: Background: Marriage and underage childbirth is a phenomenon of increasing incidence globally. Adolescent mothers simultaneously encounter multiple developmental challenges related to transition into adulthood, marriage, pregnancy and mothering responsibilities. Despite this, studies investigating postpartum care needs for adolescent mothers are limited. Aims: The aim of this study was to explore adolescent mothers' postnatal inpatient experiences and healthcare needs as they moved towards their maternal roles. Methods: A descriptive qualitative design was adopted to better understand experiences of adolescent mothers during their transition to becoming mothers. Data were collected using in-depth interviews with eleven adolescent mothers in hospital settings in South Sulawesi, Indonesia and analysed using thematic analysis. Results: Four major themes emerged: (1) breastfeeding problems, (2) disempowerment in caring for the baby, (3) health care encounters, and (4) health care needs for adolescent motherhood transition. Discussion: Breastfeeding problems and feeling disempowered in caring for their babies after birth was experienced by all adolescent mothers in this study. Furthermore, the health care provided was limited to mandatory hospital tasks with staff failing to recognize adolescent mothers' broader needs. The findings suggest that adolescent mothers need compassionate health education, support and psychological care from midwives in the postpartum ward before hospital discharge. Conclusion: The results highlight important issues in postnatal care provision for adolescent mothers in improving their maternal roles during the transition period. Specific, appropriate interventions for adolescent mothers are needed to support their transition and adaptation to their new roles.